PA.03 Outcomes of Outpatient Cervical Ripening with 1mg Dinoprostone Gel in Primiparous Singleton Pregnancy: A Cohort Study. (9th June 2014) - Stock, SJ; Norman, JE; Taylor, R; Mairs, R; Hor, K; Smith, I; Dundas, KC; Kissack, C; Azaghdani, A; Denison, FC
Abstract : Aim: To determine the safety and clinical effectiveness of outpatient cervical ripening with Dinoprostone 1 mg. Methods: Retrospective cohort study of women with singleton pregnancies having induction of labour (IOL) for postmaturity at the Royal Infirmary of Edinburgh between January 2007 and June 2010 (n = 1, 536). Women were offered outpatient cervical ripening with 1mg Dinoprostone gel if they were primiparous; had uncomplicated singleton pregnancies; and the primary indication for IOL was postmaturity (term +10 -14 days). Findings: 907 (59.1%) women were eligible for outpatient cervical ripening and 85 (5.5%) women had inpatient cervical ripening only because of preference or social indication (comparison group; n = 85). 597/907 (65.8%) in outpatient cervical ripening group completed the protocol, with median number of hours at home of 11.76 h (range 0–24.82 h). No babies were born at home. Mode of delivery, requirement for further Dinoprostone, failed IOL and neonatal unit admission rates were similar in outpatient and inpatient cervical ripening groups. The mean time to delivery was significantly longer in the outpatient group (35.45 [95% confidence interval 34.36–36.53] in outpatient group versus 22.5 [95% confidence interval 21.06–23.95] in the inpatient group p < 0.001). There was no significant difference in the total number of hours before delivery spent in hospital between the two groups (26.25 [95% CI 25.27–27.23] in outpatient group versus 24.28 [95% CI 22.5–26.0] in inpatient group; p=0.26). Conclusion: Clinical outcomes for outpatient cervical ripening are similar to those of inpatient ripening. Surprisingly, outpatient ripening did not decrease the number of hours women spend in hospital.